An Evaluation Regarding the Level of Mathematics Anxiety of the Parents of Primary School Students - Feyyaz Öztop; Veli Toptaş (Elementary Education Online, 2023)
This research was carried out to determine whether the level of mathematics anxiety of the parents of primary school students become different at the significant level according to various factors. For this purpose, it was tested whether the "Parent Oriented Mathematics Anxiety Scale" developed by the researcher is a valid and reliable method of measurement and the level of mathematics anxiety of the parent of primary school students was examined according to various factors. This research was designed based on the quantitative research paradigm and screening model. The research was conducted with the participation of the parents of primary school students who were selected on the basis of randomly and voluntarily and whose children studied in the primary schools at the center of a province in the Middle Kızılırmak Section within the fall semester of the 2017-2018 academic year. The data in the research were collected via "Parent Oriented Mathematics Anxiety Scale" and "Personal Information Form" which were developed by the researcher. Statistical technicswere applied for analyzing the data. According to research findings it was determined that“Parent Oriented Mathematics Anxiety Scale”is a valid and reliable method of measurement the level of mathematics anxiety of the parents become different at significant level according to gender, level of graduation, number of children, total monthly income, employment status, mathematics standing during studentship